Effects of the Superoxide Dismutase Mimetic Tempol on Impaired Endothelium-Dependent and Endothelium-Independent Relaxations in Type II Diabetic Rats. (April 2013) - Oniki, Hideyuki; Goto, Kenichi; Fujii, Koji; Kansui, Yasuo; Murakami, Noboru; Ohtsubo, Toshio; Matsumura, Kiyoshi; Kitazono, Takanari
<x xml:space="preserve">Abstract</x> Endothelium-derived hyperpolarizing factor (EDHF)-mediated hyperpolarization and relaxation, and endothelium-independent relaxations to the nitric oxide donor sodium nitroprusside and the adenosine 5′-triphosphate (ATP)-sensitive K+-channel opener levcromakalim were both impaired in mesenteric arteries of type II diabetic Goto–Kakizaki rats. The treatment with the superoxide dismutase mimetic tempol or its combination with the angiotensin II type 1 receptor blocker candesartan failed to improve EDHF-mediated responses, although both treatments partially improved endothelium-independent relaxations. These findings suggest that increased oxidative stress may in part account for the impaired endothelium-independent relaxations in diabetes, while it does not play a major role in the impaired EDHF-mediated responses.